Language Ability of Mild Intellectually Disabled (MID) Children: Case Study of Dina MaraMida in SLB Negeri 1 Padang - Amrina, Yasirly; Sari, Armita (J-SHMIC : Journal of English for Academic, 2019)
This study is a case study of mild intellectually disabled children. The purpose of this study is to describe the language skills of Dina Maradina as children with mild intellectual disability (MID). This research is expected to contribute educatively to actions that can be given to intellectually disabled children, especially mild intellectual disability to encourage increased language skills. At the stage of providing data, used the refer and proficient method. The basic technique used in this method is Teknik Sadap, followed by Teknik Simak Libat Cakap (SLC), Teknik Simak Bebas Libat Cakap (SBLC), Teknik Catat and Teknik Rekam as advanced techniques. Data analysis was carried out qualitatively in the form of a description of aspects of language disorders experienced by the subject of the research by describing various symptoms and language skills owned by the subject. The results showed that subjects with mild intellectual disability has good language skills. It has several disadvantages, such as the ability of subject in emotional control, the ability in focus and concentration control and the ability in language production in terms of writing production. The results showed the subject did not have a significant language disorder. The subject is able to communicate smoothly with the other person. This can be seen from the subject's ability to issue sentences that fit the context of the conversation. The subject is also able to show gestures, facial expressions, and usual expressions in accordance with the communication she does.   Keywords: Language ability, intellectual disability, neurolinguistics